(untitled) (ENTHYMEMA, 2025)
Czech structuralism is closely linked to the Prague Linguistic Circle (or Prague School), but it also developed independently of this institution during the 20th century. The theoretical and methodological legacy of Czech structuralism can be studied regarding the way in which some Czech scholars dealt with the issue of rhythm in epic literature. This study aims to briefly introduce and summarize the most important contributions of Czech structuralists to this issue. The study focuses on the ideas of Vilém Mathesius, Jan Mukařovský, Felix Vodička, Miroslav Červenka and Milan Jankovič. The core of the study is an outline of the conception of Jan Mukařovský, who in his university lectures attempted to develop a systematic plan for narrative research. The paper concludes with a summary of the main approaches of Czech structuralists to rhythm in epic literature and a reflection on the influence of new terms and concepts introduced by M. Červenka and M. Jankovič (e.g. rhythmic focus, rhythmic vocabulary, stream, etc.) on the further development of this issue.